Identification of Candida Species from Clinical Samples in a Honduran Tertiary Hospital - Montes, Kathy (Pathogens, 2019)
Candida species are one of the most important causes of human infections, especially in hospitals and among immunocompromised patients. The correct and rapid etiological identification of yeast infections is important to provide adequate therapy, reduce mortality, and control outbreaks. In this study, Candida species were identified in patients with suspected fungal infection, and phenotypic and genotypic identification methods were compared. A total of 167 axenic fungal cultures and 46 clinical samples were analyzed by HardyCHROM(®), MicroScan(®)(Omron Microscan Systems Inc, Renton, WA, USA), and PCR-RFLP (Restriction Fragment Length Polymorphisms). The species of the C. albicans complex were the most frequent, followed by C. tropicalis and C. glabrata. Less common but clinically relevant species of Candida were also isolated. The comparison between the three methods was concordant, especially for the most common Candida species. Fungal DNA amplification was successful in all clinical samples.